Health improvement through the teeth and oral health awareness and care of teeth and mouth in children for Panti Guna SLB Melati Aisyiyah Desa Bandar Khalifah - Kartia, Dewi Kartika; Boel, Trelia; Manja, Cek Dara; Nainggolan, Lidya Irani; Batubara, Fitri Yunita (Talenta Publisher, 2020)
Health is very important to always pay attention to. Healthy behavior can affect the health of everybody. Dental and oral health is a part of general health, and to keep teeth and mouth healthy can be done with the right techniques and ways to brush teeth. Based on Basic Health Research, dental and oral diseases still occur in North Sumatra province, both urban and rural. Therefore, through the Community Service Institution at USU, a community service activity was carried out under the title Improvement of Dental and Mouth Health through the Counseling for Dental and Oral Health Care for Children of Melati Aisyiah SLB Orphanage Homes in Bandar Khalifah. This activity is based on the need to maintain oral health from an early age so that good behavior in maintaining health can be accustomed from childhood. In addition, there are only a few orphanage children who realize correctly the importance of dental health for general health. Counseling on the maintenance of dental and oral health in children of the SLB Melati Aisyiyah Orphanage, Bandar Khalifah can provide a deep understanding of the importance of maintaining oral health by brushing teeth early on.